Perubahan Kualitas Hidup Lansia (WHOQOL-BREF) Sebelum dan Sesudah Intervensi untuk Meningkatkan Kadar Hidrasi Kulit di STW Cibubur - Jessica Elizabeth; Sukmawati Tansil Tan; Yohanes Firmansyah; Yana Sylvana (Jurnal Kedokteran Meditek, 2020)
A common health problem in elderly skin is dryness and itchiness. This influences the quality of life of the elderly. This study aimed to determine changes in the quality of life of the elderly holistically after an intervention to increase skin hydration. The study was conducted at STW RIA Pembangunan Orphanage in Cibubur in September 2019. This study used a quasi-experimental approach and used a WHOQOL-BREF questionnaire. This instrument was used to determine the quality of life, covering four domains such as physical health, psychology, social relations and the environment. Paired T-Test was used as statistical analysis with Wilcoxon as an alternative test. Results showed significant changes in the results of 13 out of 26 questions in WHOQOL-BREF after interventions (Q1, Q2, Q10, Q15, Q16, Q5, Q6, Q11, Q19, Q26, Q23, and Q24) at a p-value <0.05. The present study also observed an increase in all WHOQOL-BREF domain values (p-value <0.05). It can be concluded that there were significant changes in the total value in all domains between before and after interventions to increase skin hydration status (p-value <0.05).